Amyloid deposition in oral cavity and larynx, a single institute experience. (28th October 2021) - Abu-Salah, A K; Hou, T
Abstract: Introduction/Objective: Amyloidosis is characterized by extracellular accumulation of insoluble amyloid fibril. Amyloid deposition in the head and neck area is rare. Methods/Case Report: In this study, we reviewed 34 specimens from 26 patients including: 18 specimens from the larynx and/or pharynx (13 patients) and 16 specimens from the oral cavity (13 patients). The clinical presentation, related laboratory results, and pathologic finding were reviewed. Results (if a Case Study enter NA): Within the 18 laryngeal specimens were: 10 glottic, 4 supraglottic, 3 nasopharyngeal or pharyngeal wall, and 1 subglottic. Of the 16 cases from oral cavity there were 9 lingual, 3 labial, 2 palatine, 1 tonsillar, and 1 alveolar ridge. Ten out of 13 patients with laryngeal amyloid deposition had protein electrophoresis performed and only 3 of the patients had monoclonal light chain detected. Among these three patients, one had multiple myeloma, one had lymphoplasmacytic lymphoma and one had the diagnosis of plasma cell dyscrasia. Interestingly, in the patients with oral cavity amyloidosis, 10 out of 11 patients tested had abnormal findings. Six of the patients had monoclonal light chain, two demonstrated monoclonal peak of IgG kappa, one with IgG lambda and one with IgA lambda. Among these 10 patients, 6 of them had biopsy-proved or history of multiple myeloma, one patient had marginal zone lymphoma, two patients had systematic amyloidosis. Only one patient did not have any malignancy or systematic involvement identified. Conclusion: In our small cohort, the most common location of amyloid deposition in the larynx is glottis. When it involves the oral cavity, tongue is the most common location. Compared to the larynx, amyloid deposition in the oral cavity tends to be associated with hematopoietic malignancy or systematic involvement, although this finding needs to be confirmed by a larger scale of study.